The influence of board of directors’ characteristics on the environmental disclosure among Malaysian companies - Che Adam, Noriah; Lode, Nor Asma; Abd Mutalib, Hafizah (UUM Press, 2019)
The environmental activities conducted by companies have been scrutinized by the public due to the huge environmental problems faced by many people across the world. These activities are corporate social activities included in the corporate social responsibility (CSR) framework by Bursa Malaysia that informs the public regarding the social and environmental activities implemented by Malaysian companies. Data from 353 companies of various types in Malaysia revealed that the information about effective usage of energy and resources is the most disclosed item by Malaysian companies, followed by the waste management and disposal, and reusing and recycling information. The least disclosed item by Malaysian companies is prevention and reparation program. In addition, the regression results showed that the higher proportion of non-executive directors could increase the disclosure of environmental information. The results prove that the non-executive directors have played their role to increase the companies legitimacy by encouraging the management of companies to provide more environmental information. Hence, this study provides significant contribution for the supervisory bodies and policy makers in developing guidelines for Malaysian companies concerning environmental issues through environmental disclosures in their annual reports.